A Study of the Solar Wind Ion and Electron Measurements From the Magnetospheric Multiscale Mission's Fast Plasma Investigation. Issue 10 (19th October 2021) - Roberts, O. W.; Nakamura, R.; Coffey, V. N.; Gershman, D. J.; Volwerk, M.; Varsani, A.; Giles, B. L.; Dorelli, J. C.; Pollock, C.
Abstract: We compare plasma measurements in the solar wind between the Magnetospheric MultiScale Mission's (MMS) Fast Plasma Investigation (FPI) and those obtained near the Earth‐Sun L1 Lagrangian point from OMNI. FPI is an instrument designed to investigate plasma processes such as magnetic reconnection, acceleration, and turbulence. Since 2017, MMS supports solar wind campaigns where the plasma can have a higher Mach number, a cooler temperature, and a narrower beam compared with the MMS primary regions of interest. With FPI's firmware now optimized for these campaigns, the comparison with OMNI aids the interpretation of solar wind measurements. From these comparisons, we can make suggestions for both fast and burst‐survey telemetry modes. From fast mode intervals, we find first, that the FPI ion density can be lower than the OMNI proton density. However, the FPI electron density agrees well with the OMNI proton density. Second, due to the solar wind's cooler proton temperature and narrow‐angle, the FPI ion temperature is overestimated. Thus, using the OMNI proton temperature is suggested for plasma parameters such as the ion β, the ratio of ion thermal to magnetic pressure. Third, the FPI ion velocity is well‐estimated when compared with the OMNI proton velocity. In burst mode, the ion density and temperature have similar characteristics but to a lesser degree. Spin effects observed in all these plasma moments in burst mode intervals are reduced with the methods discussed in this paper. The results are summarized in a table that includes linear fit parameters and their defined errors. Key Points: Plasma measurements in the solar wind from Magnetospheric MultiScale Mission's Fast Plasma Investigation (FPI) are compared with the OMNI solar wind database The electron density and ion velocity show good agreement with OMNI's proton density and velocity respectively The FPI ion density is underestimated and FPI ion temperature is overestimated when compared to OMNI